The Effect of Music Therapy and Murottal Al-Quran Therapy on Increasing Muscle Strength and Decreasing Anxiety in Stroke Patients Undergoing Passive Range of Motion (ROM) Exercises - Ixora Ixora; Rahayu Niningasih; Dewi Wulandari (Humanistic Network for Science and Technology (HNST), 2022)
Stroke can impact various body functions, one of which is paralysis or problems controlling movement related to muscle strength. The research aimed to determine the effect of ROM exercises on increasing muscle strength in stroke patients at Dr. Soedomo Trenggalek Hospital. Researchers used a quasy experiment method with a control group pretest-posttest design. The sampling technique used purposive sampling with a sample of 30 people. Data were analyzed using the independent sample t-test and paired sample t-test. The results obtained: there was a difference in the strength of the right-hand muscle between before and after ROM exercise (p-value = 0.473); there was a difference in right leg muscle strength between before and after ROM therapy (p-value = 0.772); there was a difference in anxiety before and after ROM therapy (p-value = 0.772); there was a difference in muscle strength in the right hand before and after ROM therapy and Murrotal Al-Quran music therapy (p-value = 0.000); there was a difference in muscle strength in the right leg before and after ROM therapy and Murrotal Al-Quran music therapy (p-value = 0.000); there was a difference in muscle strength in the right hand before and after ROM therapy and Al-Quran Murrotal music therapy (p-value = 0.000; there was a difference in muscle strength in the left hand between ROM therapy and Al-Quran Murrotal music therapy (p-value = 0.000; there was a difference in right leg muscle strength between ROM therapy and Al-Quran Murrotal music therapy (p-value = 0.000; and there was a difference in left leg muscle strength between ROM exercises and Al-Quran Murrotal music therapy (p-value = 0.000). Based on the results of the study, it can be concluded that the combination of ROM therapy and murrotal Al-Quran music therapy is more effective for increasing hand and leg muscle strength and for reducing anxiety levels in patients with stroke. Keywords: music therapy; murottal Al-Quran; muscle strength; anxiety